THE IMPLIMENTATION OF ISLAMIC EDUACTION LEARNING IN PANDEMIC ERA BASE ON QURAN AND HADITH PERSPECTIVE (A CASE STUDY AT UNIVERSITY OF LAMBUNG MANGKURAT BANJARMASIN) - Evita Yuliatul Wahidah; Agus Salim; Nur Mashani Mustafidah (LPPM STAI Muhammadiyah Probolinggo, 2021)
Cases in the medical world that caused by the corona virus or known as COVID-19 (Corona Virus Disease-2019) have become a pandemic and have penetrated the educational world. It also affected Islamic education at Lambung Mangkurat University, Banjarmasin, South Kalimantan. COVID-19 pandemic has changed Islamic education arrangement that has been run orderly, causing the lost education which able to lead into lost generation. Work From Home policy, social and physical distancing, and the process of teaching and learning activities that apply the online system also enliven the dynamics of Islamic educationThis research is a qualitative type with a descriptive approach because it aims to find answers of the questions that highlight the phenomena and problems of implementing on-line courses, positive and negative impacts during the online lecture process, and problem-solving actions to overcome obstacles in the lecture process during the pandemic base on Quran and Al-Hadith perspective. This qualitative research consists of three activity plots that occur simultaneously, which are data reduction, data presentation, conclusion or verification.From the discussion which includes phenomena, problems, challenges and impacts of learning Islamic education during pandemic, there is an offer of problem solving and prospective solutions for online learning Islamic education from the perspective of the Quran and Al-Hadith. Among them: Inclusive Learning, which are mentoring teaching and learning activities to all students, Adaptability and Resilience, streamlining the role of the family as a relationship for lecturers and technology-based teaching media.